Penambahbaikan Kualiti Pengasuhan di Rumah dari Perspektif Undang-undang - Mashitah Abdul Mutalib; Intan Nadia Ghulam Khan; Rahimah Saimin; Nik Salida Suhaila Nik Saleh; Abidah Abdul Ghafar; Siti Aishah Zulkiflee (Global Academic Excellence, 2024)
Quality childcare services are essential in ensuring that children are well cared for not only in terms of their health and safety, but also their mental and intellectual development. Childcare services should not be thought of as should not be considered as mere care services but rather it is the key foundation for young children's education. According to practice in Malaysia, home childcare centres that care for less than four children do not need to register with the authorities and are not monitored by any laws or regulations. The issue of home childminders who are not regulated by specific laws is crucial to be highlighted in an effort to improve the quality of childcare services in Malaysia through legislative efforts. Hence, the purpose of this research is to examine the legal requirements for regulating home child care centres. Highlights of incidents and cases involving home day care are analysed to see the extent to which children's safety is exposed to the risk of danger as a result of the absence of specific laws to supervise home childminders. This study was conducted using the method of doctrinal research in the form of data collection based on document analysis and case reviews. The findings of this study indicate that there is a need to draft a specific law to regulate home childminders to protect the welfare and safety of children.